THE SPORT EDUCATION MODELS ON PHYSICAL ACTIVITY OF JUMPING ROPE PERFORMANCE IN ELEMENTARY SCHOOL - Ginanjar, Shela; Rihatno, Taufik; Widyawan, Dena (STKIP Muhammadiyah Kuningan, 2023)
The sports education learning model in physical education is currently widely applied by collaborating with team sports such as football, volleyball, and basketball. Regarding fitness material, very few use this sports education model. This will provide great benefits for students. The aim of this research is to test the effectiveness of learning to jump rope using the sports education learning model. The population in this study was Darussalam Elementary School, totaling 18 classes. The sample was chosen randomly and assigned to elementary school students at Darussalam Elementary School V.A. and V.B. classes, with 20 students each. The jump rope test was carried out for 1 minute, 1 minute, and 30 seconds. The results of the research show that students who study with the sports education model obtain better results than students who study with the conventional model regarding physical activity and performance in learning jump rope at Darussalam Elementary School. Teachers' skills in mastering MVPA are the key to maintaining students' fitness and health. Further studies regarding the use of this sports education model in football, volleyball, and basketball should pay attention to differences according to gender and other aspects such as student responsibility and discipline.